Effectiveness of two interactive educational methods to teach tobacco cessation counseling for senior dental students - Ahmadian, Mina (Eur J Dent, 2017)
OBJECTIVE: Nowadays, one of the major health problems in many countries is tobacco use. Dental professionals are in a unique position to promote smoking cessation since they have the opportunity for regular interaction with their patients. The purpose of the present study was to compare the effectiveness of two educational methods to teach tobacco cessation counseling (TCC) in dental practice for senior dental students. MATERIALS AND METHODS: In this interventional study, 93 eligible senior dental students from two dental schools in Tehran, Iran were randomly divided into two groups. Two educational programs, role play (RP) and problem-based learning (PBL), with the same aim about TCC in dental practice, were developed and implemented for the two groups. The score of knowledge, attitude, and skill were determined in both groups before and after participation in the course using a questionnaire. The changes in the scores from pre- to post-test were statistically analyzed using repeated measure ANOVA test. RESULTS: Total scores of knowledge, attitude, and skill of the participants showed improvements when compared to scores before training (P < 0.001, P = 0.003, and P < 0.001, respectively). However, the differences between the two study methods were statistically insignificant (P > 0.05). CONCLUSION: The results suggested that TCC training through RP and PBL methods leads to improvement in knowledge, attitude, and skills of dental students in the short-term evaluation.